2023
DOI: 10.3390/brainsci13010133
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Lithium Therapy and Thyroid Disorders in Bipolar Disorder: A Historical Cohort Study

Abstract: Lithium has been a cornerstone treatment for bipolar disorder (BD). Despite descriptions in the literature regarding associations between long-term lithium therapy (LTLT) and development of a thyroid disorder (overt/subclinical hypo/hyperthyroidism, thyroid nodule, and goiter) in BD, factors such as time to onset of thyroid abnormalities and impact on clinical outcomes in the course of illness have not been fully characterized. In this study we aimed to compare clinical characteristics of adult BD patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…If TSH does increase after starting lithium, this does not necessarily warrant lithium's discontinuation, or correction with levothyroxine. Although high‐normal TSH levels have been associated with poor antidepressant response 38 and with rapid cycling 45 and mixed states, 46,47 increased TSH levels following the initiation of lithium can frequently normalize without further intervention 32,48 . Moreover, a recent review found that the effect size for the association between hypothyroidism and clinical depression was considerably lower than previously assumed, and the modest association was possibly restricted to overt hypothyroidism and female individuals 49 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If TSH does increase after starting lithium, this does not necessarily warrant lithium's discontinuation, or correction with levothyroxine. Although high‐normal TSH levels have been associated with poor antidepressant response 38 and with rapid cycling 45 and mixed states, 46,47 increased TSH levels following the initiation of lithium can frequently normalize without further intervention 32,48 . Moreover, a recent review found that the effect size for the association between hypothyroidism and clinical depression was considerably lower than previously assumed, and the modest association was possibly restricted to overt hypothyroidism and female individuals 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Although high-normal TSH levels have been associated with poor antidepressant response 38 and with rapid cycling 45 and mixed states, 46,47 increased TSH levels following the initiation of lithium can frequently normalize without further intervention. 32,48 Moreover, a recent review found that the effect size for the association between hypothyroidism and clinical depression was considerably lower than previously assumed, and the modest association was possibly restricted to overt hypothyroidism and female individuals. 49 Early testing with aggressive response to TSH increases could lead to unnecessary treatment or lithium discontinuation.…”
Section: Also Shown Inmentioning
confidence: 93%
See 1 more Smart Citation
“…Insurance coverage is an issue in the United States; regular monitoring for Li, thyroid, and renal indices requires high copays and deductibles. The potential development of renal insufficiency 40,41 and thyroid dysfunction 42 are major concerns for Li nonprescription and even discontinuation by prescribers in the United States. 43 It is additionally possible that preference has been given to more recently approved treatments, such as SGAs and MSACs, and/or a perception of greater difficulty in using Li from the standpoint of laboratory drug monitoring and drug toxicity profile.…”
Section: These Differences Could Be Due To a Different Mean Age Of Pr...mentioning
confidence: 99%
“…Especially lithium therapists, it has proven to be the treatment of choice for BD, but its effect on thyroid function is explicit, due to the antithyroid effects of it, hypothyroidism is a common complication of it. [93,94]. What's more, supraphysiological doses of TH also appeared to be an excellent option for BD treatment [95,96].…”
Section: Treatment Of Bdmentioning
confidence: 99%